Analisis Pemasaran Syariah Pada UMKM Food Court Di Lasinrang Park Kabupaten Pinrang - Idri Parakkasi; Muslihati; Asbar (Universitas Islam Negeri Alauddin Makassar, 2024)
This research examines Sharia Marketing Analysis at MSME Food Courts in Lasinrang Park, Pinrang Regency. The research is qualitative research with a phenomenological type, which is based on findings or events that occur in the field, while the data sources used are primary and secondary data. Marketing has an important role in running a business, especially in running a business using marketing strategies in accordance with sharia which is bound and regulated. This research focuses on the marketing strategies carried out by MSMEs in Lasinrang Park, Pinrang Regency.The results of the research show that the marketing strategy of MSME players in Lasinrang Park, Pinrang Regency is running in accordance with sharia which instills attitudes and behavior that are honest, trustworthy, responsible and always prioritize customer trust by applying several indicators in the research as benchmarks for sharia marketing carried out . From various MSME actors who are different but the same goal is still to carry out healthy and good marketing in accordance with Islamic sharia. With this research, it is also hoped that it will increase enthusiasm and motivation to continue running the business well, wisely and consistently with marketing strategies in accordance with Islamic sharia.